A pH and magnetic dual-response hydrogel for synergistic chemo-magnetic hyperthermia tumor therapy. Issue 18 (8th March 2018) - Zhou, Xiaohan; Wang, Longchen; Xu, Yanjun; Du, Wenxian; Cai, Xiaojun; Wang, Fengjuan; Ling, Yi; Chen, Hangrong; Wang, Zhigang; Hu, Bing; Zheng, Yuanyi
Abstract : A pH and magnetic dual-responsive hydrogel highly sensitive to tumor acid microenvironment and efficient responsive magnetic-hyperthermia cancer eradication. Abstract : To overcome the toxicity of chemotherapy, increasing attention has been paid to local drug delivery systems (DDSs). pH-Sensitive hydrogels have emerged as promising DDS materials in the biomedical field due to their remarkable characteristics. However, the pH environment in tumor varies from person to person, which makes the applicability of systems based on pH challenging. In this study, we developed a contractible hydroxypropyl methyl cellulose (HPMC)/Fe3 O4 hydrogel with dual-response pH and magnetic properties aiming to overcome the limitations of pH-sensitive hydrogel drug delivery systems and further increase their efficiency in tumor therapy. The HPMC/Fe3 O4 hydrogel could act as a drug delivery system that combines pH-sensitive triggering and magnetic dual-response drug release for synergistic chemo-magnetic hyperthermia therapy. The drug delivery profile of the HPMC/Fe3 O4 /doxorubicin hydrochloride (DOX) hydrogel was determined in vitro and revealed a remarkable pH-sensitive performance. After synergistic chemo-magnetic hyperthermia treatment, mice with 4T1 breast cancer xenografts recovered without any recurrence or metastasis, demonstrating the synergistic effect of chemotherapy and magnetic hyperthermia therapy. Meanwhile, reduced toxicity and superior anticancer effects were achieved due to the combined effect of the pH and magnetic hyperthermia response properties. This study demonstrated the high efficacy and low toxicity of the improved design of HPMC/Fe3 O4 for drug delivery, which may provide a promising approach for the application of chemo-magnetic hyperthermia cancer therapy.